The firehouse light - Nolan, Janet; Lafrance, Marie (Berkeley [Calif.] : Tricycle Press, 2010)
Tells the true story of a lightbulb that burned inside a wooden firehouse for over one hundred years as everything around it changed.
Publisher's Weekly
School Library Journal starred
Wilson's Children
Booklist, June 2010
Horn Book, October 2010
Kirkus Review, April 2010
Keywords: Fire extinction -- California -- Livermore -- History -- Juvenile literature; Fire safety -- California -- Livermore -- History -- Juvenile literature; Fire stations -- California -- Livermore -- History -- Juvenile literature; Incandescent lamps -- California -- Livermore -- History -- Juvenile literature; Fire extinction; Fire safety; Fire stations; Incandescent lamps; Electric lamps; Fire departments -- Livermore (Calif.) -- History; Fire fighting -- Livermore (Calif.) -- History; Picture books for children